Informed consent as an ethical requirement in clinical trials: an old, but still unresolved issue. An observational study to evaluate patient's informed consent comprehension. Issue 4 (31st May 2013) - Sanchini, Virginia; Reni, Michele; Calori, Giliola; Riva, Elisabetta; Reichlin, Massimo
Abstract : We explored the comprehension of the informed consent in 77 cancer patients previously enrolled in randomised phase II or phase III clinical trials, between March and July 2011, at the San Raffaele Scientific Institute in Milano. We asked participants to complete an ad hoc questionnaire and analysed their answers. Sixty-two per cent of the patients understood the purpose and nature of the trial they were participating in; 44% understood the study procedures and 40% correctly listed at least one of the major risks or complications related to their participation in the trial. We identified three factors associated with comprehension of the informed consent: age, education and type of tumour/investigator team. We suggest several possible improvements of how to obtain informed consent that will increase patient awareness, as well as the validity and effectiveness of the clinical trials.